KONTRIBUSI PERSEPSI IKLIM ORGANISASI DAN DUKUNGAN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. ALPIN BOGA PANGAN MEDAN - Tobing, Hilde; Mutia, Cut (ANALITIKA, 2011)
This study aims to see the contribution of Climate Perception of Organization and Support of Organizational Citizenship Organizational Behavior at  PT. Alpin Boga Pangan Medan. In proving the above hypothesis, we used regression analysis method of data analysis two predictors. There is a significant positive relationship between perceptions of organizational climate and organizational support to the Organizational Citizenship Behavior. This is evidenced by the coefficient Freg = 3.838 where p <0.050. This indicates that the better the perception of organizational climate organizational culture, Organizational Citizenship Behavior is also higher. Conversely the lower the perception of organizational climate, and the lower support of the organization Organizational Citizenship Behavior is also lower. Based on these results, the hypothesis proposed been accepted.